Effects of polyphenol (carob) supplementation on body composition and aerobic capacity in taekwondo athletes - Gaamouri, N.; Zouhal, H.; Hammami, M.; Hackney, A. C.; Ben Abderrahman, A.; Saeidi, A.; Ben Ounis, O. (Physiology & Behavior, 2019)
Herbal products and supplements use by athletes has increased over the past decade. One such item being polyphenols. These are reported to reduce weight and modify body composition, which could aid athletes in many sports. Therefore, the purpose of the study was to determine the effect of 6 weeks supplementation with carob, a naturally occurring polyphenol, on body composition and aerobic capacity in youth taekwondo athletes. Twenty-three taekwondo athletes (21.9 ± 1.2 years; 1.64 ± 0.03 m; 67.4 ± 17.3 kg;BMI: 22.8 ± 5.5 kg/m2) participated in a short-term (6-week) double-blind randomized design parallel fully controlled training study (pre-to-post measurements): Supplemented group (SG), n = 11;placebo group (PG), n = 12. Body composition, aerobic capacity, heart rate and RPE were analyzed before and after 6 weeks of carob rich polyphenol ingestion. Significantly greater decreases in weight were observed for SG and PG (-2.82% and - 0.51%respectively) with differences between groups (p < 0.001). No significant differences were reported in percentage body fat and muscular volume between groups. Our results revealed an improvement of aerobic performance score and RPE with differences between groups. A cute polyphenol supplementation seemed to be effective in reducing body weight and improving aerobic performance in athletes.